Transvaginal ultrasonography and hysteroscopy as predictors of endometrial polyps in postmenopause - Godoy Borges, Pitia Carita de [UNESP]; Dias, Rogerio [UNESP]; Machado, Rogerio Bonassi; Ramos Borges, Joao Bosco; Dias, Daniel Spadoto [UNESP] (Sage Publications Ltd, 2015)
The study compared ultrasound and ambulatorial hysteroscopy as diagnostic methods detecting endometrial polyps in postmenopause women. 281 women aged 41-82 years who underwent ambulatorial hysteroscopy were analyzed for presence of uterine bleeding and/or altered transvaginal ultrasound (endometrial thickness >= 5 mm). Ultrasonography detected endometrial polyps in 22.8% of patients and endometrial thickening in the other 59.8%. Hysteroscopy diagnosed endometrial polyps in 80.8%. Ultrasonography showed sensitivity of 88.7%, specificity of 25.4%, positive predictive value of 81.7%, negative predictive value of 37.5% and accuracy of 75.4% in diagnosing endometrial polyps. Hysteroscopy showed 96.4% sensitivity, 74.6% specificity, 93.4% positive predictive value, 84.6% negative predictive value and 91.8% accuracy. Hysteroscopy demonstrated more accuracy than ultrasonography, which is not sufficient for accurate diagnosis.
Keywords: endometrial polyp; endometrial thickening; hysteroscopy; menopause; transvaginal ultrasonography